2020
DOI: 10.3390/su12219072
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Measures Recommended by the Government to Limit the Spread of Coronavirus (COVID-19) on Physical Activity Levels, Quality of Life, and Mental Health of Brazilians

Abstract: To reduce transmission of the coronavirus, the Brazilian government adopted containment measures to control the virus’ spread, including limitations to the practice of physical activity. It was aimed to analyze the effects of COVID-19 quarantine on physical activity levels, energy expenditure, quality of life, and level of stress in a sample of the Brazilian population. The sample included 426 participants (7 to 80 years). The International Physical Activity Questionnaire, Short form survey-36 (SF-36), and Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 31 publications
5
56
1
6
Order By: Relevance
“…We excluded 10 studies based on a quality assessment of the results, and 27 studies were excluded based on reasons presented in the PRISMA flow diagram (Figure 1). The range of observations covered dietary choices (14,(21)(22)(23)(24)(25)(26)(33)(34)(35)(36)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) , lifestyle changes in children (24,36,(48)(49)(50)(51) , physical activity levels (33)(34)(35)37,38,(38)(39)(40)(41)43,46,47,49,52,53,(53)(54)(55)(56)(57)(58)(59)(60) , psychosocial factors (22,23,26,38,44,<...>…”
Section: Categorization Of Determinantsmentioning
confidence: 99%
See 2 more Smart Citations
“…We excluded 10 studies based on a quality assessment of the results, and 27 studies were excluded based on reasons presented in the PRISMA flow diagram (Figure 1). The range of observations covered dietary choices (14,(21)(22)(23)(24)(25)(26)(33)(34)(35)(36)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) , lifestyle changes in children (24,36,(48)(49)(50)(51) , physical activity levels (33)(34)(35)37,38,(38)(39)(40)(41)43,46,47,49,52,53,(53)(54)(55)(56)(57)(58)(59)(60) , psychosocial factors (22,23,26,38,44,<...>…”
Section: Categorization Of Determinantsmentioning
confidence: 99%
“…Two studies were from preprints and were included after assessing their qualities individually (22,52) . The included studies had the following countries of origin: Brazil (59) , China (40,57) , Croatia (51,64) , France (47,52,56) , Jordan (58) , India (48,55) , Iraq (61) , Italy (21,23,24,35,36,45,45,53) , Korea (50) , Lithuania (39) , Netherlands (60) , Poland (25,42,51) , Spain (44,46,63) , Turkey (43,49,65,66) , United Arab Emirates (33) , United Kingdom (54) and the United States of America (26,38,41,67) . Furthermore, multi-regional studies conducted intercontinentally (22) , among eighteen countries in the Middle East and North Africa (MENA) region (34) , and Paraguay and Italian based multinational research (62) are included in our analysis.…”
Section: Categorization Of Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study De Matos et al [ 11 ] have recently shown in a sample of Brazilians that, in the period before the COVID-19 pandemic, children and adolescents of both sexes had a significant higher level of physical activity and energy expenditure, and were lower in body weight compared to the period of self-distancing imposed by COVID-19 [ 11 ].In addition, the authors emphasize that during social distancing the domains of quality of life (e.g., functional capacity, general health status, vitality, social emotional aspects and mental health) decrease significantly in children and adolescents [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2) economic support-timely treatment is provided to confirmed patients, reducing financial stress and increasing public confidence; and (3) emotional support-the media reports on front-line health caregivers and their work to prevent and control the epidemic, uplifting public confidence in the fight against the virus. Moreover, most previous COVID-19 studies have focused on determining the epidemiological and clinical characteristics of infected patients [35,36], genomic characteristics of the virus [37], global health governance challenges [34,38], and mental health studies of front-line health care providers [39][40][41]. However, the existing literature on the psychological effects of COVID-19 on the general population in China is still scarce [8], and there are only a handful of studies devoted to this issue.…”
Section: Introductionmentioning
confidence: 99%